Waste Composting for Urban and Peri-Urban Agriculture: Closing the Rural-Urban Nutrient Cycle in Sub-Saharan Africa 2001
DOI: 10.1079/9780851995489.0193
|View full text |Cite
|
Sign up to set email alerts
|

Definition and boundaries of the peri-urban interface: patterns in the patchwork.

Abstract: This chapter takes the local factors most evident in the periurban interface (PUI) of the Ghanaian city of Kumasi and considers the relevance of these factors to have common application and consequences in other cities' PUIs. Three approaches to the discussion of the nature of the PUI of Kumasi are employed. First, agricultural production is considered as well as the differences between urban, periurban and rural farming systems and changes occurring therein. Second, market and transportation systems and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2004
2004
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…In line with Adam (2001) [29], we conducted a random sampling within a given sampling extent. Unlike Adam who took an arbitrary circle, with a radius of 40 km from the city centre, we applied a travel-time approach [13] to generate the sampling extent.…”
Section: Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with Adam (2001) [29], we conducted a random sampling within a given sampling extent. Unlike Adam who took an arbitrary circle, with a radius of 40 km from the city centre, we applied a travel-time approach [13] to generate the sampling extent.…”
Section: Samplingmentioning
confidence: 99%
“…As expected, the results showed that the characteristics of those areas lying between the extremes of the urbanicity scale were not clear and unambiguous but rather patchy and "lumpy" [39] in terms of their levels of change and diversity (Figure 8). Two main areas of transition could be identified, albeit with fuzzy boundaries, representing the two "different concepts of periurbanness" [29], see also [13,17,18]:…”
Section: The Periurban: Two Areas Of Transition Along the Urban-ruralmentioning
confidence: 99%
“…Land tenure is a complex issue in periurban Kumasi as land may be held by the government for public facilities, by families (‘family land’), by the community (‘stool land’, controlled by the community chief) and by individuals. The debates around pressures of development have focused to an extent on community land (Brook & Dávila, 2000; Adam, 2001a; Kasanga, 2001; McGregor et al ., 2006). The role of the chiefs in controlling and selling land for development is critical.…”
Section: Periurban Kumasimentioning
confidence: 99%
“…The increasing pollution and waste disposal problems found in many sub‐Saharan African cities, resulting from rapid growth and urbanization, widespread poverty, inadequate and weak local governance and limited financial resources (Onibokun, 1999; Adam, 2001a; Adarkwa & Post, 2001; Drechsel & Kunze, 2001; Simon et al ., 2001; 2003), have become distinctive features of Kumasi and its immediate periurban interface that pose major challenges to environmental protection, waste management, food security and urban and periurban agriculture (Brook & Dávila, 2000; Mensah et al . , 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation